Pneumomediastinum Secondary to Barotrauma after Recreational Nitrous Oxide Inhalation - H. Jeddy; Farhan Rashid; H. Bhutta; B. Lorenzi; A. Charalabopoulos (Case Reports in Gastrointestinal Medicine)
We present a case of a seventeen-year-old patient, admitted in the care of the surgical team following inhalation of nitrous oxide at high pressure, leading to extensive pneumomediastinum and surgical emphysema. We discuss the subsequent investigations and management for this patient. In the absence of history of airway injury and respiratory problems including asthma and with no oesophageal perforation on investigations, the diagnostic and management challenges encountered have been discussed which will help in future management of similar cases.